The influence of the region between residues 220 and 344 and beyond in Phrixotrix railroad worm luciferases green and red bioluminescence - Viviani, Vadim R. [UNESP]; Da Silva Neto, Antonio Joaquim [UNESP]; Ohmiya, Yoshihiro (Oxford University Press (OUP), 2004)
To find the regions having a major influence on the bioluminescence spectra of railroad worm luciferases, we constructed new chimeric luciferases switching the fragments from residues 1-219 and from 220-545 between Phrixotrix viviani (PxvGR; λmax = 548 nm) green light-emitting luciferase and Phrixothrix hirtus (PxhRE; λmax = 623 nm) red light-emitting luciferases. The emission spectrum (λmax = 571 nm) and KM for luciferin in the chimera PxRE220GR (1-219, PxhRE; 220-545, PxvGR) suggested that the region above residue 220 of PxvGR had a major effect on the active site. However, switching the sequence between the residues 226-344 from PxvGR luciferase into PxhRE (PxREGRRE) luciferase resulted in red light emission (λmax = 603 nm), indicating that the region 220-344 by itself does not determine the emission spectrum. Furthermore, the sequence before residue 220 of the green-emitting luciferase is incompatible for light emission with the sequence above residue 220 of PxhRE. These results suggest that the fragments before and after residue 220, which correspond to distinct subdomains, may fold differently in the green- and red-emitting luciferases, affecting the active site conformation.
Keywords: Bioluminescence; Luciferases; Phrixotrix; Railroad worms; luciferase; luciferin; amino acid sequence; bioluminescence; chimera; color; controlled study; enzyme active site; enzyme analysis; light; nonhuman; phrixotrix hirtus; phrixotrix viviani; priority journal; sequence analysis; spectrum; worm; Animals; Beetles; Binding Sites; Kinetics; Luminescent Measurements; Peptide Fragments; Recombinant Proteins; Structure-Activity Relationship; Phengodidae; Phrixothrix; Phrixothrix hirtus